2008
DOI: 10.1021/mp700094s
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modeling of Corticosteroid Pharmacogenomics in Rat Muscle following Acute and Chronic Methylprednisolone Dosing

Abstract: The pharmacogenomic effects of a corticosteroid (CS) were assessed in rat skeletal muscle using microarrays. Adrenalectomized (ADX) rats were treated with methylprednisolone (MPL) by either 50 mg/kg intravenous injection or 7-day 0.3 mg/kg/h infusion through subcutaneously implanted pumps. RNAs extracted from individual rat muscles were hybridized to Affymetrix Rat Genome Genechips. Data mining yielded 653 and 2316 CS-responsive probe sets following MPL bolus and infusion treatments. Of these, 196 genes were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
41
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 25 publications
1
41
0
Order By: Relevance
“…Studies in the Jusko Laboratory have utilized Affymetrix gene arrays to monitor gene expression under controlled baseline conditions in normal rats as well as after administration of large doses of methylprednisolone (16). These studies have shown that normal rats often exhibit circadian rhythms in gene expression in liver and muscle, but the rhythms may peak at various times of the day.…”
Section: Gene Transcription Profiling As Pharmacodynamic Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in the Jusko Laboratory have utilized Affymetrix gene arrays to monitor gene expression under controlled baseline conditions in normal rats as well as after administration of large doses of methylprednisolone (16). These studies have shown that normal rats often exhibit circadian rhythms in gene expression in liver and muscle, but the rhythms may peak at various times of the day.…”
Section: Gene Transcription Profiling As Pharmacodynamic Markersmentioning
confidence: 99%
“…The latter is a severe complication in use of mRNA as a biomarker. Adding further complexity is that single-dose changes in gene expression are not predictive of responses during chronic infusions (16).…”
Section: Gene Transcription Profiling As Pharmacodynamic Markersmentioning
confidence: 99%
“…The first two observational datasets are generated by two simulation models representing pharmacogenomic pathways [37], [38], including drug kinetics/dynamics, described by difference and differential equations, respectively. These pathways are initiated by the drug stimulation and observational data are obtained as non-equally spaced time-course data.…”
Section: Introductionmentioning
confidence: 99%
“…As we will clarify in the forthcoming sections, the model parameters have been adjusted so to reproduce hmga2 gene expression data. This fitting procedure is customarily adopted in pharmacogenomics 10,11 and yields to reliable estimates for the a priori unknown kinetic rates, providing in turn a viable strategy to reconstruct the underlying genetic networks.…”
Section: Introductionmentioning
confidence: 99%